2017
DOI: 10.1016/j.jfda.2016.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of rosehips based on the content of their biologically active compounds

Abstract: In this study, an in-depth analysis of the unique set of rosehip samples from 71 Rosa genotypes was conducted with the aim to identify the most suitable ones for applications in the food and pharmaceutical industries based on the content of biologically active compounds. In the first part of our experiments, the antioxidant activity was determined by 2,2-diphenyl-1-picrylhydrazyl assay and the genotypes with the highest values were selected for the follow-up analysis. In the second part of experiments, the maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 28 publications
4
36
1
1
Order By: Relevance
“…Polyphenol compounds possess remarkable antioxidant properties and protective effects against illnesses . There are extensive distributions of individual flavonoids and phenolic acids in Rosa species fruits in terms of their type and concentration . A study conducted on five Rosa species reported concentrations of gallic acid between 7.70 and 12.93 μg g −1 DW, chlorogenic acid between 7.55 and 12.11 μg g −1 DW, caffeic acid between 6.12 and 9.38 μg g −1 DW and p ‐coumaric acid between 5.93 and 9.00 μg g −1 DW .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyphenol compounds possess remarkable antioxidant properties and protective effects against illnesses . There are extensive distributions of individual flavonoids and phenolic acids in Rosa species fruits in terms of their type and concentration . A study conducted on five Rosa species reported concentrations of gallic acid between 7.70 and 12.93 μg g −1 DW, chlorogenic acid between 7.55 and 12.11 μg g −1 DW, caffeic acid between 6.12 and 9.38 μg g −1 DW and p ‐coumaric acid between 5.93 and 9.00 μg g −1 DW .…”
Section: Resultsmentioning
confidence: 99%
“…50 There are extensive distributions of individual flavonoids and phenolic acids in Rosa species fruits in terms of their type and concentration. 6,7,14,23,[51][52][53] A study conducted on five Rosa species reported concentrations of gallic acid between 7.70 and 12.93 μg g −1 DW, chlorogenic acid between 7.55 and 12.11 μg g −1 DW, caffeic acid between 6.12 and 9.38 μg g −1 DW and p-coumaric acid between 5.93 and 9.00 μg g −1 DW. 7 The levels of caffeic acid, gallic acid, p-coumaric acid, rutin and quercetin in fruit extracts of R. canina were reported as 18.50, 4.58, 10.08, 137.75 and 6.58 mg kg −1 respectively.…”
Section: Fruit Phenolic Compositionmentioning
confidence: 99%
“…According to Andersson et al (2011), R. pimpinellifolia contains a wide range of carotenoids including mainly lycopene, prolycopene, β-carotene, γ-carotene, ζ-carotene, carotene C1, carotene C2, and carotene C3. (Bhave et al, 2017;Jakesevic et al, 2009;Porter, Van Den Bos, Kite, Veitch, & Simmonds, 2012). R. pimpinellifolia is a seasonal fruit and perishes very quickly due to its water content and biological activities.…”
mentioning
confidence: 99%
“…and consists of a significant amount of unsaturated fatty acids [ 34 , 35 ]. Other significant groups of biologically active rosehip compounds are galactolipids and unsaturated fatty acids [ 36 , 37 ]. The fatty acid composition of rosehip oil is represented by stearic (up to 4%), palmitic (5%), oleic (up to 20%), linoleic (up to 50%), and linolenic acids (up to 40%).…”
Section: Introductionmentioning
confidence: 99%
“…The fatty acid composition of rosehip oil is represented by stearic (up to 4%), palmitic (5%), oleic (up to 20%), linoleic (up to 50%), and linolenic acids (up to 40%). Lycopene makes rosehip and its products beneficial for the prevention of cardiovascular diseases and cancer [ 33 , 37 , 38 , 39 , 40 , 41 , 42 ]. Rosehip fruits have anti-inflammatory, antioxidant, antiproliferative, and antidiabetic properties [ 31 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%